GAMBARAN PRILAKU REMAJA PUTRI TERHADAP PERSONAL HYGIENE SAAT MENSTRUASI - Junay Darmawati; Lidya Fransisca (SCIENTIA JOURNAL, 2021)
The background of this research is that adolescents not only grow taller and bigger but also changes inthe body that allow them to reproduce. The purpose of this study was to describe the behavior of adolescent girlstowards personal hygiene during menstruation in STIKes Al-Su'aibah Palembang.This research method uses a descriptive survey method. The population in this study were all femalestudents at STIKes Al-Su'aibah Palembang. The sample in this study was 44 respondents who were taken byaccidental sampling.The results of the univariate analysis of 44 respondents showed that the personal hygiene of adolescentgirls during menstruation was good as many as 31 respondents (70.5%) and those who had poor personalhygiene were 13 respondents (29.5%). Adolescent girls who have good behavior during menstruation are 33respondents (75.0%), and those who have bad behavior are 11 respondents (25%).The conclusion in this study is that young women in STIKes Al-Su'aibah Palembang have good behaviorduring menstruation.